A preliminary profile of Australian women accessing doula care: Findings from the Australian Longitudinal Study on Women's Health. (6th August 2013) - Steel, Amie; Frawley, Jane; Sibbritt, David; Adams, Jon
<x xml:space="preserve">Abstract</x> Despite growing interest and controversy regarding the value of doulas in contemporary maternity care, little is known about the profile of women who choose to involve a doula in their care team. This preliminary analysis indicates that women's attitudes towards maternity care may influence their use of a doula more so than demographic factors. Further research examining these issues in more detail is needed for all those involved in maternity care to ensure safe maternal and fetal outcomes.